2017
DOI: 10.1007/s00221-017-5089-y
|View full text |Cite
|
Sign up to set email alerts
|

Finger tapping and pre-attentive sensorimotor timing in adults with ADHD

Abstract: Sensorimotor timing deficits are considered central to ADHD. However, the tasks establishing timing impairments often involve interconnected processes, including low-level sensorimotor timing and higher-level executive processes such as attention. Thus the source of timing deficits in ADHD remains unclear. Low-level sensorimotor timing can be isolated from higher-level processes in a finger-tapping task that examines the motor response to unexpected shifts of metronome onsets. In this study, adults with ADHD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
16
2
Order By: Relevance
“…These FI changes are further notable given that they could be reflective of impulsivity and or inability to inhibit responding. All of these are features of neurodevelopmental disorders such as autism spectrum disorder and attention deficit hyperactivity disorder (Coghill et al 2014;Hove et al 2017;Lambrechts et al 2018;López-Martín et al 2015;Rubia et al 2009;van Hulst et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These FI changes are further notable given that they could be reflective of impulsivity and or inability to inhibit responding. All of these are features of neurodevelopmental disorders such as autism spectrum disorder and attention deficit hyperactivity disorder (Coghill et al 2014;Hove et al 2017;Lambrechts et al 2018;López-Martín et al 2015;Rubia et al 2009;van Hulst et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We have chosen to consider ADHD in particular because in addition to the core symptoms of inattention and/or hyperactivity/impulsivity, ADHD is also characterized by deficits in motor and perceptual timing (Smith et al, 2002 ; Fair et al, 2012 ; Zelaznik et al, 2012 ; Demers et al, 2013 ; Noreika et al, 2013 ). Recent studies have revealed rhythm-related deficits in ADHD (Hove et al, 2017 ; Puyjarinet et al, 2017 ), and much of the same neural infrastructure that supports the processing of musical rhythm is implicated in ADHD, from brain circuitry (Silk et al, 2009 ; Silberstein et al, 2016 ; Mueller et al, 2017 ) and neural dynamics (Başar and Güntekin, 2008 ; Mazaheri et al, 2014 ; Loo et al, 2017 ) to dopamine signaling, with leading genetic risk factors for ADHD including dopamine gene variants (Swanson et al, 2000 ; DiMaio et al, 2003 ). Here, we propose that insights from research on musical rhythm could offer a more nuanced understanding of timing deficits in ADHD, and potentially lead to the identification of informative phenotypes, linked to neurobiological and genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent 470 with several previous studies reporting that individuals with ADHD generally exhibit more 471 variability in continuation-tapping vs. synchronization and are also more variable relative to 472 controls (Rubia et The overall emerging pattern from studying these three types of motor tapping 491 behaviors suggests the following: Individuals with ADHD seem to have an inherent deficit in 492 maintaining internal timing and generating isochronous rhythms based on internal motor-493 oscillations alone. This manifests both in their reduced ability to produce isochronous 494 spontaneous tapping as well as in increased variability in continuation tapping, that imposes 495 Supporting this distinction, a recent study suggest that the timing impairments in ADHD stem 500 from higher level factors such as sustained attention, rather than low-level sensorimotor timing 501 (Hove et al 2017). 502…”
Section: Motor Tapping Deficits In Adhd 445mentioning
confidence: 99%